Nuragic territory and ancient landscape. The Pranemuru Plateau (Sardinia) during the Bronze Age - autor, Sin (Complutum, 2005)
This book is the result of the project Nuragic Territory and Ancient Landscape in the Pranemuru Plateau; a research and heritage project in the Nuoro Province (Sardinia) sponsored by the Spanish Ministerio de Educación (project DGES PB98-0840), the Universidad Complutense (Proyecto Multidisciplinar Complutense PR269-98/196) and the Instituto del Patrimonio Histórico Español (Ayudas a Misiones Arqueológicas Españolas en el Extranjero 1999-2001). It also had the valuable support of Ph.D. Fulvia Lo Schiavo, Soprintendente Dirigente for Archaeology in the Sassari and Nuoro Provinces until 2000, the person responsible of the research project in the Arrubiu nuraghe in Orroli. This project emerges from the team’s diverse interests as regards the study of the commercial relations in the Bronze Age Mediterranean region, the analysis of landscape in past farming societies’ identity formation, and the causes, contexts and times of the Greek – Phoenician colonisation in the Mediterranean. The multidisciplinary project paid by the Universidad Complutense allowed the incorporation of geographers, who performed the GIS modelling used in the landscape study, as well as some rural development specialists who discussed the ways of making public and exhibiting the archaeological heritage in the study territory. The project team members are sincerely grateful to the Spanish institutions and Italian authorities that sponsored this work, especially Ph.D. Lo Schiavo.